Kajian Teoritik Pengaruh Hubungan Antara Geometri Jalan Dan Konsumsi Bahan Bakar Pada Unit Dump Truck - Luqman, Dzaki; Mundi, Habel; Kurniawan, Yudi (Department of Industrial Engineering, Universitas Jenderal Soedirman., 2025)
Fuel consumption in motorized vehicles is one of the main indicators of the efficiency of land transportation systems. Besides being determined by vehicle technical specifications and driver behavior, fuel efficiency is also significantly influenced by infrastructure conditions, particularly road geometry. Road geometry encompasses elements such as gradient, horizontal and vertical curvature, lane width, and road surface quality, all of which affect vehicle dynamics while driving. Roads with suboptimal geometric designs can cause increased engine workload, inefficient acceleration, and repeated deceleration, ultimately resulting in fuel waste. This study aims to examine the extent to which road geometric elements affect motorized vehicle fuel consumption. Through a literature-based qualitative and quantitative analysis approach and technical evaluation, it was found that efficient geometric design can significantly reduce fuel consumption. These findings emphasize the importance of integrating energy efficiency aspects into road planning and design processes to create a land transportation system that is not only effective and economical, but also sustainable and environmentally friendly. Keywords: Road design, energy efficiency, road geometry, fuel consumption, land transportation